Analisis System Kerja Mesin Injection ‎Molding Haitian Ma2000 Pada Produksi Super ‎Mop di PT Bolde Makmur Indonesia - Nasrudin Nasrudin; Endi Permata (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Nowadays, plastic has become a material that is inseparable from human life. Plastic is considered an easily available, practical, light and modern material. ‎In order to be able to make a plastic product that suits what we want, of course we need adequate technology, both in terms of injection machines, injection molding, materials, methods and people. The way this injection molding machine works is by putting plastic pellets into a barrel which is then heated until it melts. The melted plastic is injected into the mold which is then cooled. After that, it is released from the mold and a plastic product is formed. Current analysis produces values of 23.2 A and 20 A, which are then used to calculate power in the injection molding process. The calculation results show a power of 8.7 KW and 7.5 KW based on the data obtained.